Metabolic effects of intravenous salbutamol in the course of acute severe asthma. - Nogrady, S G (Thorax, 1977)
Peak expiratory flow rate and plasma free fatty acids, potassium, insulin, and glucose were measured in 10 patients admitted with acute severe asthma before and at frequent intervals for one hour after an infusion of salbutamol, 4 microgram/kg over 10 minutes. These studies were repeated during the recovery phase and again before discharge. Effective bronchodilatation seen after the infusion was similar in the acute and recovery phases. Baseline plasma free fatty acids were elevated but rose significantly after the infusion. There was also a significant fall in plasma potassium. These changes occurred in all individuals. There were no significant differences in mean baseline or peak changes of plasma free fatty acids, potassium or insulin on any of the study days. There was no evidence of beta receptor blockade in the acute phase in any patient.